Exclusion and self exclusion in Physical Education classes in Elementary Education II (Research, Society and Development, 2020)
Elementary education II serves adolescents aged between 11 and 14 years, during this phase pass for several transformations toward adulthood. Faced with this, School Physical Education can provide different manifestations of the body movement culture, favoring these transformations. The purpose of this study is to identify attitudes of exclusion and self exclusion of girls in Physical Education classes and the aspects that favor this event. The observations occurred in five classes of Elementary education II of a public school in the city of Boa Vista, Roraima. During Physical Education classes, we observed the exclusion and self exclusion of girls, notably due to the level of skill required in association with sports practice in class and not because the gender.